Team creative performance: exploring the relationship between team diversity and conflict affecting the creative productivity of interior design student teams - King, Hillary Smith, author; Leigh, Katharine E., advisor; Malinin, Laura H., advisor; Maynard, M. Travis, committee member (Colorado State University. Libraries, 2016)
This exploratory case study used mixed methods to examine five main variables and their possible effects on team creative productivity: team learning style diversity, student self-awareness, task conflict, process conflict, and relationship conflict. The case study incorporates 40 interior design students in teams of four, developing a design for a community service learning project. This study is primarily interested in understanding team creative performance through the process and work of interior design students. High levels of deep level diversity are believed to have positive influence on team creative process, promoting a wide variety of ideas from diverse perspectives. For this study team deep-level diversity was measured by Kolb’s Learning Style Inventory (3.1). Prior researchers have found high levels of team learning style diversity can improve team productivity, however this study found no significant relationship between Kolb learning style diversity (KLSD) and team productivity or creativity. These results may be due to lack of KLSD among student participants and/or the high number of students with bi-modal learning styles (i.e., exhibiting equal preferences for two learning styles). However, it was found that gender diversity did have a positive relationship to team creativity. No relationship was found between learning style diversity and task, process or relationship conflict. Task conflict was found to have a positive relationship to creative outcomes and low or moderate levels of process conflict were found to have a positive relationship to team productivity. Self-awareness was found to mediate conflict in sometimes unexpected ways. For example, task conflict was positive for team creativity when teams trusted each other enough to debate ideas. Students who expressed high levels of self-awareness often tended to be highly agreeable, and by seeking common ground experienced little to no task conflict. This finding suggests students may need more practice and better tools for engaging in productive task conflict leading to more creative outcomes. Process conflict at low to moderate levels was found to be positive for team productivity, however at high levels it caused relationship conflict negatively affecting team productivity. Although findings did not support a significant relationship between learning style diversity and team creative productivity, this study suggests further research is needed to understand the influence of bi-modal learners on team deep-level diversity and the effects they may have on team processes and creative productivity.
Keywords: creativity; interior design; conflict; teams; diversity